Oligoclonal selection of nanobodies targeting vascular endothelial growth factor - Ahadi, Mehrdad; Ghasemian, Haniyeh; Behdani, Mahdi; Kazemi-Lomedasht, Fatemeh (Journal of immunotoxicology, 2019)
While monoclonal antibodies are efficient therapeutics for cancer treatment, nanobodies or variable heavy domain - due to their small size, high stability, and solubility - have many advantages in comparison. Oligoclonal nanobodies are a mixture of nanobodies against different epitopes of an antigen. Specific nanobodies against vascular endothelial growth factor (VEGF, which has an important role in cancer angiogenesis) were selected from an immune camel library using biopanning. Specific binding of the nanobodies to VEGF antigen was assessed by periplasmic extract enzyme-linked immunosorbent assay (ELISA). Bioinformatics analysis and molecular docking were performed on selected nanobodies against VEGF. The in vitro inhibitory effects of each single nanobody, as well as a pool of selected nanobodies (oligoclonal nanobodies), on proliferation and tube formation by/in human umbilical vein endothelial cells (HUVEC) cells was evaluated using MTT and Tube formation assays, respectively. Four nanobodies showed the highest signal intensity in the periplasmic extract ELISA. Sequencing revealed that four unique nanobodies with different CDR3 rejoin were selected. Oligoclonal nanobodies inhibited proliferation and tube formation of the HUVEC cells more potently than did each individual nanobody. Taken together, this data from this study suggests that in vitro use of nanobodies (in an oligoclonal mode) that target distinct epitopes on VEGF could be promising as a novel therapy to treat VEGF-dependent pathologies. However, this needs to be further tested in in vivo studies.